Estimated cost per HIV infection diagnosed through routine HIV testing offered in acute general medical admission units and general practice settings in England. Issue 4 (23rd September 2015) - Ong, KJ; Thornton, AC; Fisher, M; Hutt, R; Nicholson, S; Palfreeman, A; Perry, N; Stedman‐Bryce, G; Wilkinson, P; Delpech, V; Nardone, A
Abstract : Objectives: Following national guidelines to expand HIV testing in high‐prevalence areas in England, a number of pilot studies were conducted in acute general medical admission units (ACUs) and general practices (GPs) to assess the feasibility and acceptability of testing in these settings. The aim of this study was to estimate the cost per HIV infection diagnosed through routine HIV testing in these settings. Methods: Resource use data from four 2009/2010 Department of Health pilot studies (two ACUs; two GPs) were analysed. Data from the pilots were validated and supplemented with information from other sources. We constructed possible scenarios to estimate the cost per test carried out through expanded HIV testing in ACUs and GPs, and the cost per diagnosis. Results: In the pilots, cost per test ranged from £8.55 to £13.50, and offer time and patient uptake were 2 minutes and 90% in ACUs, and 5 minutes and 60% in GPs, respectively. In scenario analyses we fixed offer time, diagnostic test cost and uptake rate at 2 minutes, £6 and 80% for ACUs, and 5 minutes, £9.60 and 40% for GPs, respectively. The cost per new HIV diagnosis at a positivity of 2/1000 tests conducted was £3230 in ACUs and £7930 in GPs for tests performed by a Band 3 staff member, and £5940 in ACUs and £18 800 in GPs for tests performed by either hospital consultants or GPs. Conclusions: Expanded HIV testing may be more cost‐efficient in ACUs than in GPs as a consequence of a shorter offer time, higher patient uptake, higher HIV positivity and lower diagnostic test costs. As cost per new HIV diagnosis reduces at higher HIV positivity, expanded HIV testing should be promoted in high HIV prevalence areas.